2013
DOI: 10.5581/1516-8484.20130033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 fatty acids on regulatory T cells in hematologic neoplasms

Abstract: The development of leukemia and lymphomas is related to the increase in inflammatory process modulators. These, in turn, have divergent actions on the neoplastic process. Populations of T cells have different roles in the neoplastic environment; while interferon-gamma positive T cells have antitumor activity, the FoxP3+interleukin-10 positive population present a pro-tumor activity. Simultaneously, the inflammatory process promotes the mobilization of fatty acids from the cell membrane to produce lipid mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…These days, ω-3 fatty acids are playing an increasingly emergent role in artificial nutrition, due to the discovery of their protective and immunomodulatory effects in inflammatory processes [20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These days, ω-3 fatty acids are playing an increasingly emergent role in artificial nutrition, due to the discovery of their protective and immunomodulatory effects in inflammatory processes [20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…-Inflammatory parameters: values of IL-6, CRP, TNF-α, IL-10, IL-8 y CD25 on Days 0, 1, 3, 5 and 21 post surgery will be recorded. These values have been selected according to what is reported in the literature in similar studies [19][20][21][22][23][24][25]. Also, these same values will be recorded pre-operatively at the time surgical intervention is indicated to show the patient's baseline inflammatory status.…”
Section: Demographic Pharmacological Clinical and Analytical Datamentioning
confidence: 99%
“…In vitro and review studies have concluded that EPA and DHA can induce apoptosis in leukaemic cell lineages (32)(33)(34)(35)(36) . Furthermore, in vitro studies performed with leukaemic cell lines have shown an increment in the antineoplastic action of drugs used in chemotherapy when EPA and DHA are present in the culture medium (28,37,38) .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the production of the less inflammatory EPA- and DHA-derived eicosanoids is increased. On the other hand, the ability of these two FAs to decrease the activity of regulatory T cells, major regulators of immune responses to leukemic cells, skews the immune response to act against hematological malignancies [ 11 ]. DHA and EPA can also prevent allergic diseases by inhibiting Th2-driven immune responses.…”
Section: In Vitro Studies On Epa and Dhamentioning
confidence: 99%
“…Dietary intake of omega-3 FAs has been also shown in human studies to inversely correlate with the overall risk of different types of malignancies such as colorectal, prostate and breast cancer [ 8 10 ]. A substantial number of in vitro studies on cancer cell lines as well as studies on animal models of cancers have shown the anti-proliferative, apoptotic, cytotoxic, and anti-metastatic properties of DHA and EPA [ 11 ]. Keeping in mind that ROS can decrease cancer cell survival [ 12 ], different mechanisms have been suggested for the anti-cancer effects of DHA and EPA such as induction of ROS and consequent peroxidation of lipids [ 13 , 14 ], changing the composition of the plasma membrane and lipid rafts [ 15 , 16 ], affecting the mitochondrial membrane potential [ 17 ] and epigenetic alteration of genes involved in apoptosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%